Ten findings about poverty in Latin America and the Caribbean - Jillie Chang; David K. Evans; Carolina Rivas Herrera (Inter-American Development Bank (IDB), 2024)
Poverty continues to challenge Latin American and Caribbean countries, with approximately one in three people in the region in poverty and one in seven in extreme poverty. This paper provides up-to-date insights through analysis of who the poor are, where they are located, and how they live in the region. First, it uses a large collection of household surveys that extend through 2023 to characterize the poor. It examines (1) how many people in the region are poor, (2) how the poor are distributed geographically within and across countries, (3) how poverty affects specific groups (e.g., women, children, Afro-descendants, and Indigenous people), (4) how much of the poverty in the region is chronic and how much is transitory, and (5) how poverty numbers have changed over time. Second, it identifies how the extreme and chronically poor live relative to others in their same countries, providing insights into policy responses. Specifically, it discusses (6) the living arrangements of the poor, (7) the assets they have access to, (8) how they earn their incomes, (9) how they access human capital services such as education and health, and (10) what access they have to social programs. While this analysis is descriptive, it may be useful both for targeting efforts and for generating new hypotheses for poverty reduction that can subsequently be tested causally.
Keywords: I25; J20; O10; O12; O15; O18; 330; poverty; development; Latin America and the Caribbean